Aerosol transmission of SARS-CoV-2? Evidence, prevention and control. (November 2020) - Tang, Song; Mao, Yixin; Jones, Rachael M.; Tan, Qiyue; Ji, John S.; Li, Na; Shen, Jin; Lv, Yuebin; Pan, Lijun; Ding, Pei; Wang, Xiaochen; Wang, Youbin; et al.
Graphical abstract: Highlights: Evidence suggests the transmission of SARS-CoV-2 via aerosols is plausible under favorable conditions. We synthesized the evidence for aerosol transmission and highlight the scenarios where SARS-CoV-2 aerosols may be pertinent to transmission. We summarize precautions and infection control strategies to mitigate aerosol transmission of SARS-CoV-2. Abstract: As public health teams respond to the pandemic of coronavirus disease 2019 (COVID-19), containment and understanding of the modes of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission is of utmost importance for policy making. During this time, governmental agencies have been instructing the community on handwashing and physical distancing measures. However, there is no agreement on the role of aerosol transmission for SARS-CoV-2. To this end, we aimed to review the evidence of aerosol transmission of SARS-CoV-2. Several studies support that aerosol transmission of SARS-CoV-2 is plausible, and the plausibility score (weight of combined evidence) is 8 out of 9. Precautionary control strategies should consider aerosol transmission for effective mitigation of SARS-CoV-2.